Decoding of the extended Golay code by the simplified successive-cancellation list decoder adapted to multi-kernel polar codes - Driss Khebbou; Idriss Chana; Hussain Ben-Azza (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2023)
This paper describes an adaptation of a polar code decoding technique in favor of the extended Golay code. Based on the bridge provided by a permutation matrix between the code words of these two classes of codes, the Golay code can be decoded by any polar code technique. Contrary to the successive-cancellation list technique which is characterized by a serial estimation of the bits, we propose in this work an adaptation of the simplified successive-cancellation list technique to polar codes equivalent to the Golay code. The simulations have achieved the performance of a maximum likelihood decoding, with the low decoding complexity of polar codes, compared to one of the universal decoders of linear codes most known in the literature.